Grammar form and function - Milada, Broukal (McGraw-Hill ESL/ELT, 2004)
Provides an approach to grammar instruction and integrates study of structures (form) with information on how to use them and what they mean (function). This book features photos that contextualize grammar and vocabulary and reinforce student recall